Spike Suppression in a Bidirectional High-Frequency Transformer-Link Inverter Using a Regenerative Snubber - Salam, Zainal; Ramli, Mohd zulkifli; Toh, L.S (2006)
This paper presents a spike suppression method for Bidirectional High-Frequency Link (BHFL) inverter using a regenerative snubber. Unlike the RCD snubber, this regenerative snubber dampens the voltage spike by charging its snubber capacitor during switch transition. The energy is then pumped back into the main power circuit. A 1kVA prototype inverter is constructed and the workability of the regenerative snubber is tested on the inverter. The results show that the voltage spike is significantly reduced. The efficiency of the inverter is also increased by about 5%.